Thermal and electrochemical impedance spectroscopy analysis of PAADDA film incorporated with Li2SO4 - Ian Pellinca Braga Caetano; Rodrigo de Siqueira Melo; Kênia da Silva Freitas; Ana Lucia Shiguihara; Jorge Amim Júnior (The Journal of Engineering and Exact Sciences)
In this paper, poly(acrylamide-co-dialidimethylamonium)-PAADDA films containing lithium sulfate (Li2SO4) were prepared by casting method from aqueous solutions. The obtained films (pristine PAADDA, PAADDA/Li2SO4-0.25% w/w, and PAADDA/Li2SO4-0.5% w/w) were characterized by means of attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), thermogravimetric analysis (TGA), and electrochemical impedance spectroscopy (EIS). ATR-FTIR spectra of PAADDA/Li2SO4 films showed the main bands of PAADDA and suggested a significative intermolecular interaction between the polymer and Li2SO4. TGA curves displayed that the thermal stability of PAADDA film is dependent on the Li2SO4 concentration. The ionic conductivity of the films followed the order: PAADDA/Li2SO4-0.25% w/w < pristine PAADDA <PAADDA/Li2SO4-0.5% w/w.